Bone marrow involvement of a patient with Niemann-Pick disease concomitant with Kartagener’s syndrome: Report of a rare case - Muzaffer Keklik; serdar sivgin; suleyman baldane; afra yildirim; olgun kontas; fatih kardas; cigdem pala; ali unal (Mediterranean Journal of Hematology and Infectious Diseases)
Niemann-Pick disease is a rare lipid storage disorder with autosomal recessive inheritance, which is characterized by accumulation of sphingomyelin and other sphingolipids in macrophages. In most cases, macrophage lipids show a non-spesific, ?ntense blue staining with Giemsa, so the term “sea blue histiocytosis” has been employed to describe this feature. Kartagener’s syndrome is a rare syndrome with autosomal recessive inheritance consisting of chronic paranasal sinusitis, situs inversus and bronchiectasis. It is accounted from half of primary ciliary dyskinesia syndromes. The correct diagnosis of this rare congenital disorder in early life is important in the overall prognosis of the syndrome. Here, we reported a case having Kartagener’s syndrome with concomitant Niemann-Pick disease, as there is no report of such case in literature.